Preparation and properties of K2NiF4-type perovskite oxides La2NiO4 catalysts for steam reforming of ethanol - 张利峰 王一平 黄群武 (Transactions of Nonferrous Metals Society of China, 2009)
The performance of La2NiO4 perovskite catalysts, prepared using a citric acid complexation method, for the steam reforming of ethanol was studied. The catalysts were characterized by X-ray diffractometry （XRD）, specific surface area measurements （BET）, thermogravimetric analysis （TGA） and scanning electron microscopy （SEM）. The experimental results show that the calcination temperature and thc amount of citric acid （CA） have a significant influence on the characteristics of the catalysts and their catalytic activity. Among the catalysts tested, the La2NiO4 catalyst calcined at 700 ℃ with n（La）：n（Ni）：n（CA） of 2：1：3 exhibits the best activity and excellent stability as well as very low coke formation.